Arthroscopic Removal of a Wire Fragment from the Posterior Septum of the Knee following Tension Band Wiring of a Patellar Fracture. (9th February 2015) - Tamaki, Yasuaki; Nakayama, Takashi; Kita, Kenichiro; Miyatake, Katsutosi; Kawasaki, Yoshiteru; Fujii, Koji; Takeda, Yoshitsugu
Abstract : Tension band wiring with cerclage wiring is most widely used for treating displaced patellar fractures. Although wire breakage is not uncommon, migration of a fragment of the broken wire is rare, especially migration into the knee joint. We describe here a rare case of migration of a wire fragment into the posterior septum of the knee joint after fixation of a displaced patellar fracture with tension band wiring and cerclage wiring. Although it was difficult to determine whether the wire fragment was located within or outside the knee joint from the preoperative plain radiographs or three-dimensional computed tomography (3D CT), we found it arthroscopically through the posterior transseptal portal with assistance of intraoperative fluoroscopy. Surgeons who treat such cases should bear in mind the possibility that wire could be embedded in the posterior septum of the knee joint.